2019
DOI: 10.3389/fnbeh.2018.00317
|View full text |Cite
|
Sign up to set email alerts
|

Social Memory and Social Patterns Alterations in the Absence of STriatal-Enriched Protein Tyrosine Phosphatase

Abstract: STriatal-Enriched protein tyrosine Phosphatase (STEP) is a neural-specific protein that opposes the development of synaptic strengthening and whose levels are altered in several neurodegenerative and psychiatric disorders. Since STEP is expressed in brain regions implicated in social behavior, namely the striatum, the CA2 region of the hippocampus, cortex and amygdala, here we investigated whether social memory and social patterns were altered in STEP knockout (KO) mice. Our data robustly demonstrated that STE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…There are many studies demonstrating a role for STEP in the regulation of plasticity and behaviour and in neurological disorders. For example, STEP KO mice present specific social memory impairment (Blazquez et al 2018). The first study of high throughput screening for STEP inhibitors reported that benzopentathiepin 8-(trifluoromethyl)-1,2,3,4,5-benzopentathiepin-6-amine hydrochloride (known as TC-2153) is a potent STEP inhibitor, which forms a reversible covalent bond with the catalytic cysteine in STEP.…”
Section: Step In Plasticity and Diseasementioning
confidence: 99%
“…There are many studies demonstrating a role for STEP in the regulation of plasticity and behaviour and in neurological disorders. For example, STEP KO mice present specific social memory impairment (Blazquez et al 2018). The first study of high throughput screening for STEP inhibitors reported that benzopentathiepin 8-(trifluoromethyl)-1,2,3,4,5-benzopentathiepin-6-amine hydrochloride (known as TC-2153) is a potent STEP inhibitor, which forms a reversible covalent bond with the catalytic cysteine in STEP.…”
Section: Step In Plasticity and Diseasementioning
confidence: 99%
“…We presume that the increased binding of MeCP2 in MEF2C and ADAM10 may lead to hippocampal memory deficits in the APP/PS1. In addition, our MeCP2 ChIP-seq analysis also found increased binding of MeCP2 to the STriatal-Enriched Protein Tyrosine Phosphatase ( STEP ), of which its absence triggers disrupted social memory retention and social patterns 61 . Thus, we suggest that increased binding of MeCP2 on the STEP gene may result in abrupt social memory deficits in the early ages of APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 63%
“…To determine whether Omp null mice have a specific deficit in STFP/food-related odorant recognition rather than an alteration in their general olfactory capacities, we next examined the social discrimination ability displayed by these mice in a resident—intruder paradigm assay ( 41 ; Figures 4F,G ). For that, a resident mouse (R) ( Figure 4F ) socially investigates a first intruder mouse (I1) ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
“…Social discrimination test, adapted from previously described procedures ( 41 , 61 ), was conducted in a specific behavioral room under standard light-dark cycle. Residents and juvenile intruders (25–40 days old) male and female mice, were tested with an equivalent sex ratio.…”
Section: Methodsmentioning
confidence: 99%